2020
DOI: 10.1111/pai.13271
|View full text |Cite
|
Sign up to set email alerts
|

The first, holistic immunological model of COVID‐19: Implications for prevention, diagnosis, and public health measures

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
219
0
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(246 citation statements)
references
References 119 publications
5
219
0
22
Order By: Relevance
“…Elucidating the underlying in ammatory mechanism of COVID-19 may aid clinicians' comprehension of the disease and clarify the deterioration in clinical course on Day 10 of illness as well as trends of laboratory ndings. [7,26] In our study, the median day of illness on ICU admission and intubation was [29] In this study, D-dimer peaked on Day 20 of illness. Recognition of these changes guided the institutional clinical practice for active surveillance for the detection of thromboembolism and early administration of prophylaxis.…”
Section: Discussionmentioning
confidence: 48%
“…Elucidating the underlying in ammatory mechanism of COVID-19 may aid clinicians' comprehension of the disease and clarify the deterioration in clinical course on Day 10 of illness as well as trends of laboratory ndings. [7,26] In our study, the median day of illness on ICU admission and intubation was [29] In this study, D-dimer peaked on Day 20 of illness. Recognition of these changes guided the institutional clinical practice for active surveillance for the detection of thromboembolism and early administration of prophylaxis.…”
Section: Discussionmentioning
confidence: 48%
“…IL-6 is also thrombogenic, which may well account for this signi cant cause of death from the virus 21 . Intense exercise also produces large quantities of IL-6 22 , which may account for the more severe clinical manifestations of infection amongst athletes 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It's supposed to be related to direct viral infection or dysregulated immune response (10,25,26). SARS-CoV-2 enters cells by binding angiotensin-converting enzyme-2 (ACE2) (27,28). Theoretically, the decrease of ACE2, caused by SARS-CoV-2 infection, would break the balance between ACE and ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data have reported that patients with preexisting comorbidities were more likely to suffer acute organ injury (7-9), which has been recently implicated as an independent risk for increased in-hospital death in COVID-19 patients (10-12). As reported by T. Guo,27.8% of the hospitalized COVID-19 patients exhibited myocardial injury (8) while up to 75% of the COVID-19 patients experienced different degree of kidney function decline (13). However, the exact role of this universal alternation has not been gured out.…”
Section: Introductionmentioning
confidence: 96%